A-LAREAL (APP LAW AND REPRODUCTIVE HEALTH): INNOVATION OF SEXUAL VIOLENCE LAW APPLICATIONS AS A PROMOTIONAL AND PREVENTIVE EFFORT - Tolak Haris; Lubis Nuril Ubaidilla; Vannia Raisha Putri Adita; M. Elyas Arif Budiman (UPT Penerbitan Universitas Jember, 2022)
Background: Adolescent are one of the targets in reproductive health. Sexual violence is considered a major adolescent health problem with short and long term effects on physical and mental health. Sexual violence is considered a major adolescent health problem with short and long term effects on physical and mental health. Correct sexual knowledge will lead adolescents towards rational and responsible sexual behavior and can help make important personal decisions related to sexuality so that they can avoid reproductive health problems. Knowledge of legal issues related to community sexual violence in Indonesia is still lacking. Purpose: The major aim of the study is to find out A-LAREAL (App Law and Reproductive Health) effective as a promotive and preventive effort to improve reproductive health. Methods: In the development of this application the method used is: ADDIE, there are stages in the method ADDIE that is Analyze (Analysis), Design (design), Development (Development), Implementation (Implementation), Evaluation (Evaluation), data collection using study literature and distributing questionnaires to 40 respondents. Results: The major findings of the research in this paper show that respondents' perceptions of A-LAREAL in the very good category (57.5%), good (32.5%), pretty good (10%). In general, the perception of health workers, legal experts, teachers and youth towards A-LAREAL is very good. It is hoped that the development of this application will soon be realized so that it becomes one of the efforts to promote and prevent reproductive health and can be immediately used by the wider community. Conclusion: With this application, it is hoped that adolescent, parents, teachers, and the public can use ALAREAL in accessing information about reproductive health education, legal assistance, counseling, and sharing.